Parental stress and physical violence against children during the second year of the COVID-19 pandemic: results of a population-based survey in Germany - Alina Geprägs; David Bürgin; Jörg M. Fegert; Elmar Brähler; Vera Clemens (BMC, 2023)
Abstract Background Parents and caregivers belonged to those with the highest burdens during the COVID-pandemic. Considering the close link between parental stress and child maltreatment, identifying families with high parental stress is of utmost importance to prevent violence against children. Within this study, we thus aimed to investigate the interplay of parental stress, changes in parental stress, and physical violence against children during the second year of the COVID-pandemic on an exploratory level. Methods We conducted a cross-sectional, observational study in Germany from July to October 2021. By using different sampling steps, a representative probability sample of the German population was generated. A subsample of these participants with children under the age of 18 was included for analysis within this study (N = 453, 60.3% females, Mage = 40.08; SD = 8.53). Results Higher parental stress levels were associated with more physical violence against children, higher levels of own experiences of child maltreatment, and mental health symptoms. An increase in parental stress during the pandemic was associated with female sex, the use of physical violence against children, and parental experience of child maltreatment. Parents who have ever used physical violence against their children have been characterized by higher parental stress levels, a stronger increase in parental stress during the pandemic, own experience of child maltreatment, mental health symptoms and sociodemographic characteristics. Higher parental stress levels, a stronger increase of parental stress during the pandemic, having pre-existing psychiatric disorders, and parental experience of child maltreatment predicted an increased use of physical violence against children during the pandemic. Conclusions Our results underscore the importance of parental stress for the risk of physical violence against children, more so in times of overall increased stress due to the pandemic and underline the need for low threshold support for families at risk in times of crises.